Diterpene synthases from Leonurus japonicus elucidate epoxy-bridge formation of spiro-labdane diterpenoids. Issue 1 (14th February 2022) - Wang, Jian; Mao, Yaping; Ma, Ying; Yang, Jian; Jin, Baolong; Lin, Huixin; Tang, Jinfu; Zeng, Wen; Zhao, Yujun; Gao, Wei; Peters, Reuben J; Guo, Juan; et al.
Abstract: Spiro-9, 13-epoxy-labdane diterpenoids are commonly found in Leonurus species, particularly in Leonurus japonicus Houtt., which is a medicinal herb of long-standing use in Asia and in which such spiro-heterocycles are present in at least 38 diterpenoids. Here, through generation of a transcriptome and functional characterization of six diterpene synthases (diTPSs) from L. japonicus, including three class II diTPSs (LjTPS1, LjTPS3, and LjTPS4) and three class I diTPSs (LjTPS5, LjTPS6, and LjTPS7), formation of the spiro-9, 13-epoxy-labdane backbone was elucidated, along with identification of the relevant diTPSs for production of other labdane-related diterpenes. Similar to what has been found with diTPSs from other plant species, while LjTPS3 specifically produces the carbon-9 (C9) hydroxylated bicycle peregrinol diphosphate (PPP), the subsequently acting LjTPS6 yields a mixture of four products, largely labda-13(16), 14-dien-9-ol, but with substantial amounts of viteagnusin D and the C13- S / R epimers of 9, 13-epoxy-labda-14-ene. Notably, structure–function analysis identified a critical residue in LjTPS6 (I420) in which single site mutations enable specific production of the 13 S epimer. Indeed, extensive mutagenesis demonstrated that LjTPS6:I420G reacts with PPP to both specifically and efficiently produce 9, 13 S -epoxy-labda-14-ene, providing a specialized synthase for further investigation of derived diterpenoid biosynthesis. The results reported here provide a strong foundation for future studies of the intriguing spiro-9, 13-epoxy-labdane diterpenoid metabolism found in L. japonicus . Abstract : Elucidated epoxy-bridge formation of spiro-9, 13-epoxy-labdane diterpenoids through functional characterization of diterpene synthases from L. japonicas .